The Role Of Msmes Digitalization In Increasing The Income Of Bahari Indah In Tonyaman Village, Binuang District - Nurfadila , Siti; Dambe , Jumriani; Salmawati , Salmawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The Digitalization of MSMEs is the process of utilizing digital technology across various aspects of business operations and management. This includes the use of the internet, software, hardware, and other digital platforms. According to data from the Ministry of Trade (Kemendag) in 2023, the total value of digital or e-commerce transactions reached IDR 533 trillion. This figure marks a sharp increase compared to the previous year's value of IDR 476 trillion. This significant growth underscores the importance of digitalizing businesses in the current era. This study aims to examine the role of digital technology in maximizing the products of the Micro, Small, and Medium Enterprise (MSMEs) Bahari Indah. This research employs a field research approach, using both primary and secondary data sources. The methods used for data collection include interviews and documentation. The data obtained are presented descriptively and analyzed using an inductive reasoning approach. The findings of this study conclude that digital technology plays a significant role in maximizing the products of Bahari Indah MSMEs, contributing to an increase in sales volume. Bahari Indah MSMEs has begun implementing e-marketing by utilizing digital technology to optimally achieve marketing objectives and to develop or adapt marketing concepts in order to promote products more broadly and communicate within a global scope. The form of digital technology primarily used is social networking. In this context, Bahari Indah focuses on using Facebook as the main platform for promoting its products to the wider public. This strategy has proven effective in attracting consumer interest and encouraging purchases.